Gambaran Kualitas Hidup Pasien Tb Paru Di Puskesmas Desa Lalang Kecamatan Medan Sunggal Tahun 2023: Overview of the Quality of Life of Pulmonary TB Patients at the Lalang Village Health Center, Medan Sunggal District in 2023 - Ice Septriani Saragih,; Friska Sembiring,; Pretty Yeyen Citra Lerian Gulo, (Jurnal Midwifery, 2024)
Introduction Pulmonary tuberculosis is an infectious disease caused by Mycobacterium tuberculosis germs, these germs enter the human body through inhaled air then enter the breathing and into the lungs, the incoming germs can spread from the lungs to other parts of the body through the circulatory system, lymph duct system, through the respiratory tract (bronchus) and spread to other parts of the body. This study aims to determine the picture of the quality of life of Pulmonary TB patients at the Lalang Village Health Center, Medan Sunggal District 2023. Method Research this study used a descriptive research design. The population in this study is all lung TB patients in the Lalang Village Health Center, Medan Sunggal District, totaling 63 people. The sampling technique used is total sampling, which amounted to 63 samples. The instrument used is the Kidney Disease Quality of Life Short Form 36 (KDQOL SF 36) questionnaire. Results research show that from 63 respondents, 35 people (55.6%) had low quality of life and 28 people (44.4%) from 63 respondents. Conclusion explained most of the quality of life of Pulmonary TB patients at the Lalang Village Health Center, Medan Sunggal District in 2023 in the low category is 35 people (55.6%).